From Kabuliwala to Kesari : Mapping the (Mis)representations of Afghans in Hindi films - Mohammad Reyaz; Kaifia Ancer Laskar (ReOrient, 2025)
Indians and Afghans have shared memories, cultural and historical linkages. Besides Kabul being a part of the Mughal Empire for a long time, more than half of the Pashtuns living to the east of the Durand Line were part of undivided India (present-day Pakistan) during the British rule. With most Indian cities having significant Afghan residents, Afghans/Pashtuns got special attention in popular narratives, including in Hindi films. In movies like Kabuliwala (1961) , Khuda Gawah (1992), Kabul Express (2006) , Kesari (2019) , and Panipat (2019) , Bollywood has presented different shades of Afghans on celluloid. The popularity of Indian films among Afghans is well known, but there is hardly any academic deliberation on the representation of Afghans in Hindi films. Drawing upon Stuart Hall’s Representation and Edward Said’s Orientalism theories, the paper seeks to fill this gap. Using a semiotic approach and critical discourse analysis this paper flags the tropes of misrepresentation of Afghans in Hindi films. This paper foregrounds the majoritarian discourse around Afghans in the popular imagination in India drawing upon the binaries of loyal/traitor, rational/brutal, benevolent/vengeful, patriots/potential dangers, and sophisticated/tribal. The paper concludes that Islamophobia and the larger anti-Muslim rhetoric playing out in India have contributed to the vilification of Afghans on screen even though the two countries shared cordial political relations.